HYDROLOGICAL INVESTIGATION OF GROUNDWATER UNDER SALT AFFECTED LAND IN SHORKOT AREA WITH SPECIAL EMPHASIS ON SEEPAGE FROM LINK CANALS - Iqbal, N.; Rafiq, M.; Hashmi, Z.; Latif, Z.; Ghaffar, A. (The Nucleus, 2014)
Groundwater studies were carried out at Rechna Doab near the confluence of the rivers Chenab and Ravi, around the two link canals (HC and TSLC). The effects of canals on groundwater recharge was investigated with stable and radioactive isotope tracer technique by taking 39 spatial samples and 20 vertical profile samples at two locations . The studies show that about half of the study area receives more than 50% contribution from the canals in the groundwater recharge. The age of groundwater base flow without any contribution from the canals is more than 50 years, while the canal water component moves faster having residence time within few years. However, it seems that the hydraulic pressure due to contribution of the canals, hinders the movement of base flow coming from the northeast direction (eastern bank) and as a result, salt contents of groundwater and soil salinity increase very significantly in the area receiving little or no contribution from the canals. The study looks at horizontal and vertical extent of ground water quality at head-end of the canals. The findings of the study can help policy makers to devise policies to remove inequity due to variation in surface flow and resulting ground water quality at head and tail-ends of canal. The future studies can look at willingness to pay by low-enders for head-enders using groundwater and vice versa.